A good-performance glucose sensor fabricated via rationally designing a new cobalt–metal–organic framework precursor. (20th August 2020) - Han, Chao; Nie, Lei; Han, Xiao; Zhuang, Xiaoli; Zhang, Jingrui; Rui, Yulan; Meng, Wei
Abstract : A good-performance glucose sensor based on Co3 O4 has been first synthesized by rationally designing a new cobalt–metal–organic framework precursor. Abstract : A good-performance glucose sensor based on Co3 O4 has been first synthesized by rationally designing a new cobalt–metal–organic framework precursor, having the structural formula of [Co(Cia)2 (bmb)] n (Cia = 5-((4-carboxybenzyl)oxy)isophthalic acid, bmb = 1, 4-bis(2-methylbenziidazol-1-ylmethyl)benzene). The Co-MOF precursor exhibits one-dimensional chains in molecular structures, which are further extended to form a 3D framework via hydrogen bonds. The Co-MOF crystals show a separated columnar shape and are further stacked into micro-flower clusters. Then, the micro-flower clusters of Co-MOF precursors are transformed into Co3 O4 with a curved sheet morphology by treatment at 450 °C in air. The Co3 O4 -modified glassy carbon electrode (Co3 O4 /GCE) is applied as a glucose sensor, which works well both at a low glucose concentration range of 0.001–2 mM and high concentration range of 2–8 mM with sensitive sensitivities of 254.21 μA mM −1 cm −2 and 102.80 μA mM −1 cm −2, respectively. Moreover, Co3 O4 /GCE exhibits good anti-interference, reproducibility and stability. This study aims to not only provide an example to fabricate Co3 O4 with diverse morphologies but also affords a strategy to explore more effective electrode materials as high-performance electrochemical sensors.